Adaptive leaf morphology and anatomy of Rhizophora apiculata under environmental gradients in Tulic, Argao, Cebu, Philippines with implications for conservation - TRICIA JOY JARAPAN; MILLISCENT FLORES; DIANA ROSE CUIZON; CHRISTINE MAE ROBLE; AARON NIÑO LANANTE; DEXTER YBURAN; CHARIZ NIÑA ENAL; MEKHAILA EMNACEN; SYLVESTER T. CORTES; JOSEPH JOEL N. ALMAGRO; ZERRY AYN Z. RETUBADO; ANNE S. LORCA (Society for Indonesian Biodiversity, 2025)
Abstract. Jarapan TJ, Flores M, Cuizon DR, Roble CM, Lanante AN, Yburan D, Enal CN, Emnacen M, Cortes ST, Almagro JJN, Retubado ZAZ, Lorca AS. 2025. Adaptive leaf morphology and anatomy of Rhizophora apiculata under environmental gradients in Tulic, Argao, Cebu, Philippines with implications for conservation. Biodiversitas 26: 2978-2991. Mangrove forests provide critical ecosystem services, including coastal protection, biodiversity conservation, and carbon sequestration. However, they are increasingly threatened by environmental stressors, such as salinity fluctuations, habitat degradation, and climate change. Understanding species-specific adaptive responses to these stressors is essential for developing effective conservation strategies. This study investigated how coastal gradients and canopy light zones influence the morphological and anatomical leaf traits of Rhizophora apiculata in Tulic, Argao, Cebu, Philippines. A total of five quadrats of 5x5 m were placed in each of the landward, midward, and seaward zones. In each zone, environmental parameters including soil salinity, pH, and light intensity were recorded. Leaf samples were collected and analyzed for length, width, and anatomical features using the nail polish and potato impression method. Results demonstrated pronounced leaf plasticity in seaward individuals, with significant variations in width-related traits, while landward individuals exhibited limited morphological flexibility. The middle canopy zone showed strong adaptation to variable light conditions, with spongy mesophyll development and petiole length contributing notably to physiological performance. These findings suggest the role of leaf trait plasticity in enhancing the resilience of R. apiculata to changing environmental conditions. Incorporating trait-based approaches into mangrove conservation and restoration planning can strengthen ecosystem stability and sustain the protective and ecological functions of mangrove forests under different stressors.